The effect of inquiry learning model on mathematical problem solving abilities in terms of grade X high school students learning style - Risno Risno; Sri Sulasteri; Suharti Suharti; Fitriani Nur; Muhammad Rusydi Rasyid (Math Didactic: Jurnal Pendidikan Matematika, 2021)
This experimental research with a factorial design aims to describe the ability to solve mathematical problems of students if they applied the inquiry learning model and direct learning model, as well as to determine the interaction of learning styles with inquiry learning models on the ability to solve math problems of class X students of SMAN 4 Luwu Utara. Sampling used technique purposive sampling and obtained a sample of 68 students from a population of 238 students of class X SMAN 4 Luwu Utara. The research instrument is in the form of a learning style questionnaire and test questions on the ability to solve math problems. The data analysis used descriptive statistics and inferential statistics in the form of a 2-way Anova test. The result of the calculations reveal that there are difference in the ability to solve math problems by learning to follow the inquiry learning model and not, there is no significant difference in the ability to solve math problems between students with the inquiry model learning and the direct model in terms of their learning styles but there is an interaction between the inquiry learning model and the ability to solve math problems when viewed from the student’s learning style.